Meteorological Characteristics during Periods of Greatly Reduced PM2.5 Concentrations in March 2020 in Seoul - Il-Soo Park; Moon-Soo Park; Sang-Heon Kim; Yu Woon Jang; Joonsuk Lee; Jeffrey S. Owen; Chang-Rae Cho; Joon-Bum Jee; Jung-Hoon Chae; Minsoo Kang (Aerosol and Air Quality Research)
Abstract In March 2020, the average concentration of PM2.5 in Seoul decreased by 44% compared to that in March 2019 (from 45 µg m−3 to 25 µg m−3). In this study, the synoptic and local meteorological conditions during the period with reduced PM2.5 concentrations were analyzed. The synoptic meteorological conditions during March 2020 show a common characteristic of strong zonal flow and winds. Therefore, air circulation was active and meteorological conditions were unfavorable to long-range transboundary transport. Local meteorological conditions such as wind and turbulent motion at the surface were sensitive to PM2.5 concentrations. Our analyses indicate that the greatly reduced PM2.5 concentrations were mainly influenced by synoptic rather than local conditions. Decreased demand for heating of buildings due to warmer temperatures in March 2020, the economic slowdown following the outbreak of COVID-19, and the implementation of guidelines aimed at controlling particulate matter (PM) were other important causes of reduced PM2.5 emissions. A decrease in long-range transboundary transport contributed to the reduced PM2.5 concentrations.